2003
DOI: 10.1074/jbc.m213036200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression in Liver from a Murine Model of Hyperhomocysteinemia

Abstract: Cystathionine ␤-synthase (CBS) deficiency causes severe hyperhomocysteinemia and other signs of homocystinuria syndrome, in particular a premature atherosclerosis with multiple thrombosis. However, the molecular mechanisms by which homocysteine could interfere with normal cell function are poorly understood in a whole organ like the liver, which is central to the catabolism of homocysteine. We used a combination of differential display and cDNA arrays to analyze differential gene expression in association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 54 publications
(55 reference statements)
5
48
1
Order By: Relevance
“…In addition, the induction of HO-1 by homocysteine in cultured cells is also consistent with the increase in HO-1 expression observed in a murine model of hyperhomocysteine- mia (37). In contrast, ER stress fails to stimulate HO-1 expression in cultured hepatoma cells (38).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the induction of HO-1 by homocysteine in cultured cells is also consistent with the increase in HO-1 expression observed in a murine model of hyperhomocysteine- mia (37). In contrast, ER stress fails to stimulate HO-1 expression in cultured hepatoma cells (38).…”
Section: Discussionsupporting
confidence: 68%
“…CBS -/-mice showed severe growth retardation and most of them died within two weeks after birth. Plasma homocysteine levels in CBS -/-mice were higher in this study compared with previous studies, 401.66 ± 38.67 M vs. 205 ± 86 M, respectively (Robert et al, 2003a). This difference in homocysteine levels may be caused by a standard laboratory diet given in this study, instead of a special diet, in order to avoid the effect of diet therapy.…”
Section: Discussioncontrasting
confidence: 48%
“…The administration of pyridoxine putatively stimulates residual CBS activity. For the pyridoxine non-responsive group, a methionine-restricted, cysteine-supplemented dietary therapy (Robert et al, 2003a) should be employed even though its effectiveness is restricted. Pyridoxine, folic acid and vitamin B12 have continued to be administered in pyridoxine non-responders because they are cofactors of methionine metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies with the CBS deficient mice revealed the importance of intracellular redox balance for nitric oxide bioactivity and endothelial function, and the importance of ER stress in abnormal hepatic accumulation of lipid [92,93] . Expression of several genes analyzed by DNA microarray was found to be reproducibly abnormal in the livers of heterozygous and homozygous CBS-deficient mice [94] . These genes encode ribosomal protein S3a and methylthioadenosine phosphorylase, suggesting cellular growth and proliferation perturbations may occur in homozygous CBS-deficient mice liver.…”
Section: Approaches For Study Of Hhcymentioning
confidence: 99%